2014
DOI: 10.3390/polym6051333
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of FRP-Confined Concrete-Filled Steel Tube Columns

Abstract: This paper presents the results of an experimental study into the behavior of concrete-filled steel tube columns confined by fiber-reinforced polymer (FRP). Eleven columns were tested to investigate the effects of the FRP layer number, the thickness of the steel tube and concrete strength on their load capacity and axial deformation capacity. The experimental results indicated that the FRP wrap can effectively confine the concrete expansion and delay the local buckling of the steel tube. Both the load capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(31 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Sundarraja and Prabhu [2] studied experimentally the behavior of steel tubes filled with concrete and partially wrapped with Carbon Fiber Reinforced Polymers (CFRP) under axial compressive loads. They showed that CFRP provided effective confinement, delayed local buckling occurrence, and increased ultimate bearing capacity in agreement with the results of Lu et al [3] and the experimental and numerical results of Shen et al [4]. They concluded that unwrapped areas exhibited strains increase that led to local buckling occurrence at these areas.…”
Section: Introductionsupporting
confidence: 77%
“…Sundarraja and Prabhu [2] studied experimentally the behavior of steel tubes filled with concrete and partially wrapped with Carbon Fiber Reinforced Polymers (CFRP) under axial compressive loads. They showed that CFRP provided effective confinement, delayed local buckling occurrence, and increased ultimate bearing capacity in agreement with the results of Lu et al [3] and the experimental and numerical results of Shen et al [4]. They concluded that unwrapped areas exhibited strains increase that led to local buckling occurrence at these areas.…”
Section: Introductionsupporting
confidence: 77%
“…Concrete Filled Tube (CFT) structures are widely used in engineering due to their excellent structural and constructional performance [1,2]; this is especially the case for typical forms of Concrete Filled Steel Tube (CFST) structures [3][4][5][6][7][8][9][10]. Attention also has been paid to Concrete Filled Fiber Reinforced Polymer (FRP) Tubes, in view of their anti-corrosion properties, which can be better adapted to corrosive environments than CFST [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…A number of experimental studies [15,16] on SSCFST have been conducted to understand its mechanical performance, and design theory [17] was proposed accordingly. Some models have been developed to predict the load capacity of the FCFST columns [18,19]; however, the effect of the expansion of the concrete was not considered.…”
Section: Introductionmentioning
confidence: 99%